2023
DOI: 10.1021/acs.jpclett.2c03698
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Auxiliary Basis Set Approach for the Electronic Excitation Spectra of Organic Molecules

Abstract: We report a minimal auxiliary basis model for time-dependent density functional theory (TDDFT) with hybrid density functionals that can accurately reproduce excitation energies and absorption spectra from TDDFT while reducing cost by about 2 orders of magnitude. Our method, dubbed TDDFT-ris, employs the resolution-of-the-identity technique with just one s-type auxiliary basis function per atom for the linear response operator, where the Gaussian exponents are parametrized across the periodic table using tabula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…Single-point energies were, however, found to be prone to the errors introduced by the lacking handling of the mixed Cartesian/spherical auxiliary functions used in the aCD scheme, in agreement to the findings of Lehtola. 114 However, it is interesting to compare the findings of Hellmann et al to the recent work of Zhou et al, 137 who found that TDDFT excitation energies of organic molecules can be captured to 0.06 eV error with just a single(!) s-type auxiliary basis function per atom.…”
Section: Auxiliary Basis Setsmentioning
confidence: 94%
“…Single-point energies were, however, found to be prone to the errors introduced by the lacking handling of the mixed Cartesian/spherical auxiliary functions used in the aCD scheme, in agreement to the findings of Lehtola. 114 However, it is interesting to compare the findings of Hellmann et al to the recent work of Zhou et al, 137 who found that TDDFT excitation energies of organic molecules can be captured to 0.06 eV error with just a single(!) s-type auxiliary basis function per atom.…”
Section: Auxiliary Basis Setsmentioning
confidence: 94%
“…In the LT-G 0 W 0 /BSE calculations, we have shown that the computational time is now dominated by the BSE calculation. Based on our three guiding principles, we aim to achieve similar improvements also for the BSE in the future by making use of, for example, minimal auxiliary basis sets 72 or simplified integrals. 73,74 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: Discussionmentioning
confidence: 99%
“…Single-point energies were, however, found to be prone to the errors introduced by the lacking handling of the mixed Cartesian/spherical auxiliary functions used in the aCD scheme, in agreement to the findings of Lehtola 112 . However, it is interesting to compare the findings of Hellmann et al to the recent work of Zhou et al 135 , who found that TDDFT excitation energies of organic molecules can be captured to 0.06 eV error with just a single(!) s-type auxiliary basis function per atom.…”
Section: Auxiliary Basis Setsmentioning
confidence: 92%